Past, Present, and Future of Non-invasive Brain Stimulation Approaches to Treat Cognitive Impairment in Neurodegenerative Diseases: Time for a Comprehensive Critical Review - Sanches, Clara; Stengel, Chloé; Godard, Juliette; Mertz, Justine; Teichmann, Marc; Migliaccio, Raffaella; Valero-Cabré, Antoni (Frontiers in Aging Neuroscience, 2021)
Low birth rates and increasing life expectancy in developed societies have placed an unprecedented pressure on governments and the health system to deal with the human, social and financial burden associated to aging-related diseases. At present, ~24 million people worldwide suffer from cognitive neurodegenerative diseases, a prevalence that doubles every five years. Pharmacological therapies and cognitive trainingn have generated temporary hope and, occasionally, proof of mild relief. Nonetheless, these approaches are yet to demonstrate a meaningful therapeutic impact and changes in prognosis. We here review evidence gathered for nearly a decade on non-invasive brain stimulation (NIBS) aiming to limit cognitive decline associated with neurodegenerative conditions. Transcranial Magnetic Stimulation (TMS) and Transcranial Direct Current Stimulation (tDCS), two of the most popular NIBS technologies, use electrical fields generated non-invasively in the brain to long-lastingly enhance the excitability/activity of key brain regions contributing to relevant cognitive processes. The current comprehensive and critical review presents proof-of-concept evidence and meaningful cognitive outcomes of NIBS in eight of the most prevalent neurodegenerative pathologies affecting cognition: Alzheimer’s Disease, Parkinson’s Disease, Dementia with Lewy Bodies, Primary Progressive Aphasias, behavioral variant of Frontotemporal Dementia, Corticobasal Syndrome, Progressive Supranuclear Palsy and Posterior Cortical Atrophy. We analyzed a total of 70 internationally published studies: 33 focusing on Alzheimer’s disease, 19 on Primary Progressive Aphasia and 16 on the remaining neurodegenerative pathologies. The therapeutic benefit and clinical significance of NIBS remains inconclusive, in particular given the lack of a sufficient number of double-blind placebo-controlled randomized clinical trials using multiday stimulation regimes, the heterogeneity of the protocols, and adequate behavioral and neuroimaging response biomarkers, able to show lasting effects. The field remains promising but, to make further progress, research efforts need to take in account the latest evidence of the anatomical and neurophysiological features underlying cognitive deficits in these patient populations. Moreover, as the development of in-vivo biomarkers are ongoing, one could consider a scenario in which NIBS will be part of a cognitive rehabilitation program, or useful as a potential adjunct to drug therapies since the most early stages of such diseases.